Penggunaan Media Gambar dalam Peningkatan Kemampuan Menulis Deskriptif Siswa Kelas 5 SDN 10 Sembawa - Mayang Sari; Weny Novyanza; Darwin Effendi; Hetilaniar Hetilaniar (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to improve the descriptive writing skills of fifth-grade elementary school students through the use of picture media. The research was motivated by the low level of students’ descriptive writing ability, such as difficulties in expressing ideas, limited vocabulary, and a lack of coherence in paragraph organization. The research employed a Classroom Action Research (CAR) design carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. The participants were 28 fifth- grade students of SDN 10 sembawa selected purposively. Data were collected through writing tests, classroom observations, and documentation, and then analyzed using both qualitative descriptive and quantitative methods. The findings reveal that the use of picture media helps students observe objects in detail, enrich their vocabulary, and stimulate their imagination to construct more coherent descriptive paragraphs. The average score of students’ descriptive writing improved from 65 in the pre-cycle to 76 in the first cycle and 86 in the second cycle. This significant increase demonstrates that picture media effectively supports students in developing ideas and expressing them in well-structured written form. Moreover, students showed higher enthusiasm and motivation during the learning process. The study recommends that Indonesian language teachers integrate picture media as an alternative and engaging strategy for teaching descriptive writing, enabling learning objectives to be achieved more effectively.